Unpacking the effects of brand authenticity on consumer trust and loyalty in nutrition: a psychological perspective - Lyu, Mingkun; Wang, Shikai; Zhang, Jinwei (Frontiers in Nutrition, 2026)
BackgroundBrand authenticity plays a crucial role in shaping consumer evaluations in nutrition markets, where product claims are difficult to verify and consumers rely heavily on trust.ObjectiveThe research investigates the influence of perceived brand authenticity on consumer trust and loyalty, and also examines the mediating role of perceived sincerity, self-congruence, and emotional attachment in that connection.MethodUsing survey data from 300 consumers, the measurement and structural models were validated through Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) with bootstrapped indirect effects.ResultsThe results demonstrate that brand authenticity significantly enhances trust (β = 0.54, p < 0.001), and that trust strongly predicts loyalty (β = 0.47, p < 0.001). The indirect effect of authenticity on loyalty through trust was significant, indicating full mediation. Additional indirect pathways by sincerity, self-congruence, and emotional attachment were also supported.ConclusionThese findings clarify the cognitive and affective mechanisms linking brand authenticity to trust and loyalty in nutrition branding, offering strategic insights for managers aiming to strengthen long-term consumer relationships. In this way, the study addresses the trust and authenticity nexus during nutrition branding and demonstrates how to credibly and systematically approach brand storytelling in critical health issues.